Assessing user feedback and clinical outcomes when using a novel sleeve attachment device providing reduced activation force and a built in dose counter for pressurised metered dosage inhalers - Mapondela, Kassim (Department of Paediatrics and Child Health, 2026)
Background: Activating pressurised metered dose inhalers (pMDI) is often challenging for children. Easy Squeezy (ES), is a novel sleeve attachment device that reduces this activation force by from 46N to 12.6N and monitors the remaining doses using its built-in counter. Objectives: The primary objective of this study was to examine the usability and patient experience of the ES sleeve attachment device in the paediatric patient population and, to assess clinical outcomes (lung function, asthma control and quality of life) when using a novel sleeve attachment device for pressurised metered dose inhalers (pMDI) compared to using pMDI without the novel sleeve attachment. Methods: The usability cross-sectional study included 40 participants between the ages of 5 to 10 years, half of whom had prior experience in using a pMDI. Participants and their parents recorded their responses on the ease of use, perceptions and satisfaction with using the pMDI alone and the pMDI with the ES. The longitudinal cohort clinical study included 55 asthmatic children between the age of 5 and 12 years randomised into two groups. One group used ES for 6 weeks while the other group used pMDI. After 6 weeks the participants crossed over to the other group. Lung function test parameters were measured before randomisation and after each 6 weeks of device use. Quality of life information (PAQLQ) and child asthma control test (C-ACT) were measured after each period of device use. Results: The participants and their parents preferred ES to pMDI alone and felt happier using the ES device (100% in experienced vs 95% in inexperienced). They felt it was easier for them to activate the pMDI using ES. They expressed that the built-in counter in ES will make it easier to keep track of the doses. There was no significant difference in the baseline lung function between the groups in the clinical study. ES group had significantly lower percentage difference between pre- and post-bronchodilator FEV1 ( -6.5±15.7; FEV1/FVC: 2.5±7.5) vs (FEV1: 3.5±14.6; difference in FEV1: 3.4±13.8; FEV1/FVC: -2.6±7.4). Although no significant differences were observed in PAQLQ scores between the groups, more patients in the ES group had improvement of PAQLQ than the group using pMDI alone. Total C-ACT scores were significantly higher for the ES group. Conclusion: The Easy Squeezy device improves patient satisfaction and asthma control and may improve users' quality of life. Key words: Keywords: Pressured metered dose inhaler, children, Easy Squeezy, quality of life, lung function, asthma, asthma control.